2016
DOI: 10.1089/cyber.2015.0553
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Threats of Social Media Websites: Twitter and the Proana Movement

Abstract: 1 Questa è la versione pre-print (prima bozza) dell'articolo "Risks and threats of social media websites: Twitter and the pro-Ana movement" degli autori Bert F, Gualano MR, Camussi E, Siliquini R., pubblicato come Original Paper sulla rivista Cyberpsychology, behaviors and social networking. AcknoledgmentsThe authors declare that they have not received grants or funding for this work. Conflict of InterestThe authors declare that they have no competing interests. Abbreviation:AN -Anorexia Nervosa EDNOS -Eating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…In our analysis, we found that pro-ana websites represented approximately one-third of the online material. This finding can be compared with that obtained by a research carried out in Italy by Bert and collaborators 30. They systematically retrieved 341 “pro-ana” Twitter accounts and analyzed them in terms of number of followers (mean followers 2360.9, range 5–32,700), tweets (mean tweets: 4351.2, range: 5–85,700), and biographical information of the users (97.9% girls, mean age 17.9 years, range 12–28 years).…”
Section: Discussionsupporting
confidence: 60%
“…In our analysis, we found that pro-ana websites represented approximately one-third of the online material. This finding can be compared with that obtained by a research carried out in Italy by Bert and collaborators 30. They systematically retrieved 341 “pro-ana” Twitter accounts and analyzed them in terms of number of followers (mean followers 2360.9, range 5–32,700), tweets (mean tweets: 4351.2, range: 5–85,700), and biographical information of the users (97.9% girls, mean age 17.9 years, range 12–28 years).…”
Section: Discussionsupporting
confidence: 60%
“…In recent years, groups supporting anorexia nervosa in several ways (endorsement and promotion of dysfunctional eating behavior, maintenance of the disorder, and interference with recovery) have been spreading across social media platforms. The dynamics of the Proana Movement, which promotes behaviors relating to anorexia nervosa, have been examined using Twitter, finding that adhering people and/or promoters were almost totally teenage girls (31). In the midst of the factors mediating the risk to develop body dissatisfaction or EDs, one study focused on teenagers' offline social environment, finding that a positive mother-adolescent relationship can exert a protective function against the adverse effects of social media usage on body perception (50).…”
Section: Presentation Of Eating Disorders On Social Media Platformsmentioning
confidence: 99%
“…Several reasons that are not mutually exclusive may explain this finding. First, Twitter has a policy of excluding pro-ana content [ 32 ]. Second, the pro-ana community may communicate through other web-based means, such as pro-ana websites [ 33 ].…”
Section: Discussionmentioning
confidence: 99%